THE EFFECT OF SEAWEED (Eucheuma cottonii) ADDITION TO THE QUALITY OF WETNOODLE - Adha, Windara Nur; Loekman, Suardi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this research was to determine the effect of seaweed (Eucheumma cottonii) addition to the quality of wet noodles. The benefits of this research was to provide information about processing of wet noodles with adding seaweed flour. This study was conducted using a completely randomized design (CRD) with 4 levels treatments, M0 (withoutseaweed flour), M1 ( 5% seaweed flour), M2 ( 10% seaweed flour ), M3 ( 15% seaweed flour ) , The parameters tested were organoleptic, proximate analysis, and analysis of Total Plate Count analysis. The best treatment based on organoleptic analysiswas adding10% of seaweed flour (M2) with appearance 7.48, texture 7.08, odor 6.84, and flavor 6.92), and water content of 46.3% , protein content 5.3%, fat content of 1.98, and crude fiber 10.6%.Keywords: wet noodle, seaweed, flour, quality